2019
DOI: 10.4240/wjgs.v11.i7.303
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing neoadjuvant radiotherapy for resectable and borderline resectable pancreatic cancer using protons

Abstract: Approximately 25% of patients diagnosed with pancreatic cancer present with non-metastatic resectable or borderline resectable disease. Unfortunately, the cure rate for these “curable” patients is only in the range of 20%. Local-regional failure rates may exceed 50% after margin-negative, node-negative pancreatectomy, but up to 80% of resections are associated with regional lymph node or margin positivity. While systemic drug therapy and chemotherapy may prevent or delay the appearance of distant metastases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A phase-II clinical trial revealed that neoadjuvant FOLFIRINOX followed by individualized chemoradiotherapy enabled a high prevalence of R0 resection and prolonged survival (27). Radiotherapy delivered with protons and stereotactic body radiation may be beneficial to treatment of pancreatic cancer (28,29). It is necessary to conduct further research on the role of radiotherapy in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A phase-II clinical trial revealed that neoadjuvant FOLFIRINOX followed by individualized chemoradiotherapy enabled a high prevalence of R0 resection and prolonged survival (27). Radiotherapy delivered with protons and stereotactic body radiation may be beneficial to treatment of pancreatic cancer (28,29). It is necessary to conduct further research on the role of radiotherapy in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…125 I seeds can continuously release a low dose of γ-ray when they are implanted into tumor tissue. It can damage the DNA of tumor cells and induce apoptosis of tumor cells, so as to kill the proliferative cancer cells[ 17 , 18 ]. The advantages of 125 I seeds in the treatment of pancreatic cancer are local adaptation and low dose continuous therapy[ 19 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA of tumor cells in the proliferative period is in the late stage of synthesis and mitosis and is extremely sensitive to gamma rays. A small number of gamma rays can destroy DNA, preventing tumor cell proliferation[ 20 , 21 ]. After implantation into tumor tissue, 125 I seeds can continuously release low-dose gamma rays to kill tumor cells, damage the DNA of tumor cells, inhibit tumor cell proliferation, and induce tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%